2014
DOI: 10.1007/s12013-014-0009-2
|View full text |Cite
|
Sign up to set email alerts
|

Exploration on Mechanism of a New Type of Melatonin Receptor Agonist Neu-p11 in Hypoxia–Reoxygenation Injury of Myocardial Cells

Abstract: To explore the mechanism of a new type of melatonin receptor agonist Neu-p11 in hypoxia-reoxygenation injury of myocardial cells. Hypoxia/reoxygenation (H/R) model of H9c2 myocardial cells was established, and the cells were divided into control group, H/R group, and Neu-p11 group. Apoptosis rates of myocardial cells in different groups, the contents of creatinine kinase (CK), lactic dehydrogenase (LDH), superoxide dismutase (SOD), and malondialdehyde (MDA) in cell culture media were compared. Myocardial cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…We and others have previously demonstrated that melatonin's cardioprotective effect was partially mediated by its membrane receptors. Luzindole, a specific melatonin membrane receptor antagonist, inhibited its protective actions . In this study, both in vivo and in vitro data demonstrated that activation of Notch1/Hes1 signaling by melatonin treatment was abolished by luzindole administration.…”
Section: Discussionmentioning
confidence: 50%
“…We and others have previously demonstrated that melatonin's cardioprotective effect was partially mediated by its membrane receptors. Luzindole, a specific melatonin membrane receptor antagonist, inhibited its protective actions . In this study, both in vivo and in vitro data demonstrated that activation of Notch1/Hes1 signaling by melatonin treatment was abolished by luzindole administration.…”
Section: Discussionmentioning
confidence: 50%
“…Neu-P11 has proved antidepressant and anxiolytic effects based on its interaction with 5HT1A/1D receptors; this effect correlates with the fact, that compared to melatonin, Neu-P11 presents better affinities for these receptors (16). In addition, Neu-P11 has demonstrated to be protective against myocardial ischemia/reperfusion injury in vitro (20).…”
Section: Discussionmentioning
confidence: 90%
“…Besides its neurological actions, Neu-P11 has demonstrated usefulness in reducing intraocular pressure (17). More recently, it has proven to be protective against myocardial ischemia/reperfusion injury in vitro (20).…”
Section: Introductionmentioning
confidence: 99%
“…Neu-p11, as a novel melatonin receptor agonist, has the advantages of longer halflife, higher selectivity, less adverse reactions and easy synthesis compared with melatonin [25,26], which has great potential for clinical application. In this study, we found that Neu-p11 triggers mitochondrial translocation of NOX4 in U-CH1 and M-Chor chordoma cells, leading to mitochondrial oxidative damage and mediating NLRP3 inflammasome-dependent cell pyroptosis in chordoma cells.…”
Section: Introductionmentioning
confidence: 99%